Greek and Roman mythology A to Z - Daly, Kathleen N.; Rengel, Marian (New York : Facts On File, 2004)
Contains over five hundred alphabetically arranged entries that provide information on the major figures, places, stories, objects, and themes in Greek and Roman mythology, and includes illustrations, a bibliography, an index, and cross-references.
Cover title: Greek & Roman mythology A to Z.
Originally published: c1992, in series: Daly, Kathleen N. Mythology A to Z.
Includes bibliographical references (p. 138-139) and index.
Booklist.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Senior High School.
Keywords: Mythology, Classical -- Juvenile literature; Mythology, Classical; Classical mythology